Reduction of cerebral infarct size by dronedarone - Engelhorn, Tobias; Schwarz, Marc A.; Heusch, Gerd; Dörfler, Arnd; Schulz, Rainer (Cardiovascular Drugs and Therapy, 2011)
In the ATHENA trial, dronedarone reduced the incidence of stroke in patients with atrial fibrillation. Since smaller cerebral infarcts are sometimes asymptomatic, the reduced incidence of stroke might reflect reduction of infarct size (IS) by dronedarone. However, no data on this effect of dronedarone are available.In 60 rats, the middle cerebral artery was occluded (MCAO) for 1 h followed by reperfusion. IS was assessed at day 7. Animals were examined using a neurological 5 points score. Twelve animals served as controls (group A), 12 animals received 30 mg/kg (group B) and 100 mg/kg (group C) dronedarone daily starting 3 days before MCAO; 12 animals received 30 mg/kg (group D) starting 2 h after MCAO. In all groups treatment was maintained until day 7. In 12 additional animals (6 controls, 6 pretreated animals) fractional anisotropy (FA) was assessed using magnetic resonance imaging (MRI).IS in group A was 151 ± 45 mm(3) versus 94 ± 42 mm(3) in group B, 79 ± 29 mm(3) in group C, and 127 ± 51 mm(3) in group D, respectively (B,C,D P < 0.05 vs. A). Neuroscores and weight loss (expressed as percent of initial weight) were less in treatment groups: 1.8 ± 0.6 and 91% in group B, 1.4 ± 0.5 and 93% in group C, and 2.1 ± 0.6 and 89% in group D compared to 2.4 ± 0.5 and 83% in controls (B,C,D P < 0.05 vs. A). FA in the ischemic penumbra was significantly higher in treated than in control animals (0.44 ± 0.2 vs. 0.35 ± 0.17; P < 0.05).Dronedarone administered before and after MCAO reduces IS and improves FA and neurological outcome in transient cerebral ischemia.
EVALuna2:22954